Family Policy Models and Family Policy Outcomes - A Nordic Perspective - Heikki Hiilamo (Luxembourg Income Study (LIS), 2002)
Constructing typologies or categories of welfare states characterized social policy research during the last decade. Esping-Andersen's Three Worlds of Welfare Capitalism (1990) launched an avalanche of typologies. Interest in cross-national comparisons has been facilitated by several attempts to construct theoretical models that could capture or summarize the similarities and differences in contemporary family policies employed in Western industrial countries. However, contrary to welfare state classifications, there is so far very little - if any - empirical evidence at the institutional or the individual level to support any family policy typology. This analysis tries to validate the characteristics of the ideal Nordic family policy model at the outcome level by using micro-data comparisons between countries representing different family policy models. The micro datasets are used to describe the outcomes of family policy models. The unique characteristics of Nordic family policy are based on the country-specific features suggested by earlier research. These characteristics are summarized into six indicators on outcome level, which, in turn, are operationalized and calculated for micro datasets on example countries of different family policy models. We have as our point of reference a limited number of countries with different family policy traditions.
Keywords: 330; Familie; Familienpolitik; Mikroökonometrie; Welt; Nordeuropa